32.6k views
0 votes
Find the product. (6y − 2)2

2 Answers

7 votes

Final answer:

To find the product of (6y - 2) squared, we apply the formula for squaring a binomial and get the product as 36y^2 - 24y + 4.

Step-by-step explanation:

The question asks to find the product of the binomial (6y - 2) squared. To find the product, we use the formula for squaring a binomial: (a - b)2 = a2 - 2ab + b2. Applying this formula to our binomial:

  1. a = 6y, so a2 = (6y)2 = 36y2.
  2. b = 2, so b2 = (2)2 = 4.
  3. The middle term is -2ab = -2(6y)(2) = -24y.

Combining these terms gives 36y2 - 24y + 4 as the final product.

User Thomaszter
by
5.0k points
10 votes

Answer:

36y² - 24y + 4

Step-by-step explanation:

(6y - 2)² = (6y - 2)(6y - 2)

Each term in the second factor is multiplied by each term in the first factor, that is

6y(6y - 2) - 2(6y - 2) ← distribute both parenthesis

= 36y² - 12y - 12y + 4 ← collect like terms

= 36y² - 24y + 4

User Blacklabelops
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.